Adaptive Hybrid Case-Based Neuro-Fuzzy Model for Intrusion Detection and Prevention for Smart Home Network - Davies, I.N; Taylor, O.E; Anireh, V.I.E; Bennett, E.O (International Journal of Computer Sciences and Engineering, 2024)
The advent of Internet-of-Things (IoT) technology has ushered in a new era of unprecedented interconnectivity, by transforming our living space into a dynamic ecosystem. The challenging part of this is the security risk it poses on the network. Due to the vulnerabilities that are usually associated with smart devices, integrating them within the smart home ecosystem presents significant concern for the need of preserving data privacy, network traffic classification, and proper management of trusted devices. Various techniques have been employed in the development of Network Intrusion Detection System (NIDS) to safeguard the network against the evolving nature of attack deployed by cyber-criminals. This paper presents an Adaptive Hybrid Case-Based Neuro-Fuzzy System (HCBNFS) technique to the development of a robust and efficient Intrusion Detection and Prevention System (IDPS). The HCBNFS technique deploys the CBR as a detection engine to easily detect already known traffic patterns on the network, while the NFIS was deployed as a tuning factor to the reverse phase of the CBR to further investigate unknown traffic to the detection engines case-base. Five network packet features were selected as input variables to the proposed model. These features are the source IP, destination IP, source port, destination port, and network protocol. The model was trained using the CIC-IoT2022 dataset. For this study, the CIC-IoT2002 and a synthetic dataset were used for both testing and evaluating the performance of the system. The experimental results of the system using the CIC-IoT2022 dataset achieved 99% accuracy rate in intrusion detection, and recorded 99.5% for precision, recall, and F1-Score. The empirical evaluation of the proposed model validates its effectiveness and contributes towards the development of a more robust intrusion detection and prevention system. By enhancing data confidentiality, privacy, and security, the model represents a significant step forward in the safeguarding IoT-based smart home network against cyber-criminals.